Integrative taxonomy reveals multiple lineages of the spider genus Cybaeus endemic to the Ryukyu Islands, Japan (Arachnida : Araneae : Cybaeidae) - Ihara, Yoh; Koike, Naoki; Nakano, Takafumi (Invertebrate systematics, 2021)
The epigean spiders of the genus Cybaeus L. Koch, 1868 are known to have diversified in western North America and the Japanese Archipelago. To date, ∼80 species of Cybaeus are known from Japan, but they have not previously been recorded from the Ryukyu Islands that harbour a diversity of endemic species. Here we describe eight new species of Cybaeus from the Ryukyu Islands, extending the range of Cybaeus southward to the central Ryukyus. Both sexes of each of the new species are described, and their phylogenetic relationships are estimated using nuclear and mitochondrial gene markers. Although Cybaeus okumurai, sp. nov. and C. kumadori, sp. nov. possess genital features that are common in the other Japanese congeners, the other six species (C. yakushimensis, sp. nov., C. kodama, sp. nov., C. amamiensis, sp. nov., C. aikana, sp. nov., C. tokunoshimensis, sp. nov., and C. hikidai, sp. nov.) are characterised by an elongated embolus and tubular spermathecae. These unique genital characteristics and the phylogeny recovered here suggest that these features evolved independently among the Japanese and Ryukyu Cybaeus species. Phylogenetic analyses highlight an unusual biogeographical pattern in which C. yakushimensis and C. kodama endemic to Yakushima Island in the northern Ryukyus are related to species distributed in the central Ryukyus. In contrast, our phylogeny suggests that C. okumurai from Tanegashima Island in the northern Ryukyus is sister to C. ashikitaensis (Komatsu, 1968), distributed in Kyushu of the Japanese Archipelago. The retreat constructs and sympatric distribution of Cybaeus found among the Ryukyus are also briefly discussed.